In Defense of Hans Goedicke - Shanks, Hershel (The Biblical archaeology review, 1982)
The Washington Journalism Review, supposedly a monitor of media fairness and accuracy, has falsely and irresponsibly accused Professor Hans Goedicke of The Johns Hopkins University of attempting to pull off an academic fraud.a In the article by Washington Post reporter Lee Lescaze, the Washington Journalism Review charged Goedicke, head of the Department of Near […]